Assessment of hepatoprotective activity of Caralluma cicatricose against CCl4-induced liver damage in rabbits - Al-Mehdar, Ali A.; Dammag, Mohammad A.; Hussien, Taha A. (Journal of Drug Discovery and Therapeutics, 2015)
Liver disease has become one of the serious health problems as it is exposed to many kinds of xenobiotics and therapeutic agents. Certain medicinal plants had been used to cure some liver diseases. The present study aimed to evaluate the hepatoprotective effect of Methanolic Extract of Caralluma cicatricose (MECC) in rabbits with acute liver injury induced by carbon tetrachloride at a single dose of 1.25 ml/kg b.w. as a mixture with olive oil. MECC was administered in doses of (0.5, 1 and 1.5 g/kg b.w.) via oral gavage by intragastric tube for 8 days. The SGOT, SGPT, ALP, total protein, creatinine, blood urea nitrogen and blood glucose level were measured and histopathology of liver was performed. The results of the rabbits treated with MECC were compared with that of Liv-52. C. cicatricosa showed a significant dose-dependent reduction (P< 0.05) in the hepatic enzymes levels, blood urea nitrogen, blood glucose level and improvement of serum protein. The histopathological studies in the liver of rabbits also supported that C. cicatricosa extract markedly reduced the toxicity of CCl 4 and preserved the histoarchitecture of the liver tissue to near-normal structure. These results suggested that C. cicatricose may be acting as a natural hepatoprotective agent that prevents hepatic injury induced by CC1 4 and this may be due to its active phytoconstituents such as flavonoids and glycosides which present in the plant.